Pendayagunaan Limbah Ban Bekas Berbasis Steam Menjadi Kursi - Gumelar, Setyo (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Used tire waste is a serious environmental problem that requires creative handling. In Ketawangrejo Village, the accumulation of used tire waste has a negative impact on the environment, so an effective recycling strategy is needed. This research uses the STEAM (Science, Technology, Engineering, Arts, Mathematics) learning method to process used tire waste into chairs, with the aim of reducing waste, improving technical and artistic skills, and producing products with high selling value. The Research and Development (RnD) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model was applied in this research. The results show that chairs made from used tire waste received very high marks in idea, creativity, appearance and usefulness, with an average score above 86%. By integrating the STEAM method, this research succeeded in overcoming the problem of used tire waste and created a chair that is functional, aesthetic, environmentally friendly and economical, and was well received by respondents.